2013
DOI: 10.1021/cm303513y
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Carbon Nanoparticles of Tunable Size and Wall Thickness by Hydrothermal Treatment of α-Cyclodextrin Templated by F127 Block Copolymers

Abstract: On the basis of the strategy of forming supermolecular structure between αcyclodextrin and poly(ethylene oxide), a facile synthesis process has been successfully developed for producing hollow carbon nanoparticles of controllable size and morphology by hydrothermal treatment of α-cyclodextrin in the presence of Pluronic F127 as a soft template. The hollow carbon nanoparticles thus derived are demonstrated to exhibit excellent hydrophilic behavior. Their sizes and wall thicknesses can be tuned by adjusting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 43 publications
2
60
0
Order By: Relevance
“…0.82, indicating the graphitic nature of the N-doped carbon capsules. 31 These results are consistent with previous works that also use polydopamine as the carbon precursor. 30,31,33,34 3.5 Rigid ellipsoidal PDA capsules as effective absorbents for dyes in contaminated water…”
Section: 33supporting
confidence: 92%
See 2 more Smart Citations
“…0.82, indicating the graphitic nature of the N-doped carbon capsules. 31 These results are consistent with previous works that also use polydopamine as the carbon precursor. 30,31,33,34 3.5 Rigid ellipsoidal PDA capsules as effective absorbents for dyes in contaminated water…”
Section: 33supporting
confidence: 92%
“…29 In addition, calcinations at very high temperature more than 800 C and the dried state is a common way to turn organic carbon precursors into carbon materials. [30][31][32][33][34] It is highly challenging, if not impossible, to directly burn polymeric capsules into carbon capsules without losing their original morphology. 26 In the case of non-spherical capsules, to keep the shape intact under afore-mentioned harsh conditions is even more elusive since the whole surface does not experience the same stress or strain due to the different surface curvatures.…”
Section: 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Raman scattering spectra agree well with the XRD result, and the scattering peaks found at 1334 (D band, corresponding to disordered sp 2 hybridized carbon network) and 1595 cm −1 (G band, corresponding to ordered sp 2 hybridized carbon network) are the characteristics of the carbonized materials with polycyclic aromatic carbon sheets [37,38]. From Raman scattering spectra it is also observed that the intensity ratio of D band to G band (I D :I G ) significantly increases after functionalization of HMCSs with ArSO 3 H groups; moreover, the ratio (0.51, 0.65 and 0.76 for HMCSs, ArSO 3 HHMCSs1.8-1 and ArSO 3 H-HMCSs3.2-1) continuously increases with ArSO 3 H loading.…”
Section: Characterization Of the Catalystssupporting
confidence: 77%
“…The solvothermal reaction of bovine serum albumin in water and ethanol could produce hollow carbon nanospheres [12]. Also carbonization of self-assembled cyclodextrin with Pluronic F127 in water produced homogeneous hollow carbon nanoparticles with sizes ranging from 200 to 400 nm [13]. In this contribution, we report a novel simple approach to highly uniform hollow carbon nanospheres using carbohydrate as the carbon source in non-coordinating solvent.…”
mentioning
confidence: 99%